2015
DOI: 10.1007/s11934-015-0512-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Penile Thrombophlebitis (Mondor’s Disease)

Abstract: Superficial penile thrombophlebitis or penile Mondor's disease (PMD) is an underreported condition that causes anxiety and embarrassment in affected men. Patients usually present with a smooth, cord-like induration on the dorsal penile shaft 1-7 days after prolonged or intensive sexual intercourse, but other presentations of disease and triggers for endothelial damage are possible. The condition is typically self-limited with expected spontaneous resolution within 4-8 weeks of initial presentation, and absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 48 publications
1
18
1
3
Order By: Relevance
“…Previous reports of PMD assert an incidence of approximately 1.39%-a high risk-in men 20-40 years of age with no claims of pain ( 14 , 15 ). Studies have found that the risk factors of PMD fit Virchow's triad ( 14 - 17 ), as follows: vessel-wall damage due to vigorous sexual activity, vacuum erection device, penile trauma, etc.…”
Section: Epidemiology and Etiologymentioning
confidence: 96%
See 2 more Smart Citations
“…Previous reports of PMD assert an incidence of approximately 1.39%-a high risk-in men 20-40 years of age with no claims of pain ( 14 , 15 ). Studies have found that the risk factors of PMD fit Virchow's triad ( 14 - 17 ), as follows: vessel-wall damage due to vigorous sexual activity, vacuum erection device, penile trauma, etc.…”
Section: Epidemiology and Etiologymentioning
confidence: 96%
“…Studies have found that the risk factors of PMD fit Virchow's triad ( 14 - 17 ), as follows: vessel-wall damage due to vigorous sexual activity, vacuum erection device, penile trauma, etc. ; blood stasis, such as prolonged erection (including with the use of a PDE5 inhibitor), prolonged sitting position, and bladder overdistension; and hypercoagulation, such as urogenital infection, prostate biopsy, and hematological disease ( 14 ).…”
Section: Epidemiology and Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…La tromboflebitis de la vena superficial del pene (Enfermedad peniana de Mondor), es una entidad rara y poco frecuente que afecta principalmente a hombres en etapa productiva de la vida (entre los 20 y 57 años). Para el año 2015, no se contaba con más de 50 casos descritos en la literatura mundial 6 ; actualmente sólo se dispone de una referencia suramericana 7 y no hay casos descritos en la literatura médica colombiana. En su patogénesis se ha postulado como eje central factores o condiciones que alteran el balance de la tríada de Virchow (ver ►Tabla 1).…”
Section: Discussionunclassified
“…El caso expuesto tuvo como detonante de la enfermedad un coito vigoroso, a la ecografía doppler de pene presentó los signos radiológicos clásicos para enfermedad peniana de Mondor, recibió manejo médico en la fase aguda -subaguda Tabla 1 Factores asociados con la aparición de la Enfermedad de Mondor (todos los factores afectan el balance de la tríada de Virchow -daño endotelial, estasis venosa, estado procoagulante) 3,6,19,21,23 de la enfermedad y de forma similar a las experiencias descritas en la literatura mundial alcanzó un desenlace clínico favorable ya que presentó resolución sintomática tras dos semanas de manejo conservador y en el seguimiento clínico ejecutado tras un mes de ocurrido el evento agudo no presentó alteraciones anatómicas o funcionales significativas.…”
Section: Discussionunclassified